Antibiotic exposure is associated with minimal gut microbiome perturbations in healthy term infants - Alain J. Benitez; Ceylan Tanes; Elliot S. Friedman; Joseph P. Zackular; Eileen Ford; Jeffrey S. Gerber; Patricia A. DeRusso; Andrea Kelly; Hongzhe Li; Michal A. Elovitz; Gary D. Wu; Babette Zemel; et al. (Microbiome)
Abstract Background The evolving infant gut microbiome influences host immune development and later health outcomes. Early antibiotic exposure could impact microbiome development and contribute to poor outcomes. Here, we use a prospective longitudinal birth cohort of n = 323 healthy term African American children to determine the association between antibiotic exposure and the gut microbiome through shotgun metagenomics sequencing as well as bile acid profiles through liquid chromatography-mass spectrometry. Results Stool samples were collected at ages 4, 12, and 24 months for antibiotic-exposed (n = 170) and unexposed (n = 153) participants. A short-term substudy (n = 39) collected stool samples at first exposure, and over 3 weeks following antibiotics initiation. Antibiotic exposure (predominantly amoxicillin) was associated with minimal microbiome differences, whereas all tested taxa were modified by breastfeeding. In the short-term substudy, we observed microbiome differences only in the first 2 weeks following antibiotics initiation, mainly a decrease in Bifidobacterium bifidum. The differences did not persist a month after antibiotic exposure. Four species were associated with infant age. Antibiotic exposure was not associated with an increase in antibiotic resistance gene abundance or with differences in microbiome-derived fecal bile acid composition. Conclusions Short-term and long-term gut microbiome perturbations by antibiotic exposure were detectable but substantially smaller than those associated with breastfeeding and infant age.